2010
DOI: 10.1007/s11199-010-9877-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Effects of Acute Stress on Spatial Ability

Abstract: Although reports that men and women differ in spatial ability are common, recent research examining stress effects on spatial navigation have not included analyses of gender differences. The current study investigated cue perception and mental rotation after an acute cold-water hand immersion stress in 156 undergraduates from the western United States. Gender differences were observed in spatial performance and spatial anxiety. Discriminant analysis revealed that distal gradient cue identification and mental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…Others have previously reported higher spatial anxiety, as measured by the SAS or questionnaires specific to the individual study, in women compared to men (Bryant, 1982;Castelli et al, 2008;Gabriel et al, 2011;Lawton, 1994;Lawton & Kallai, 2002;Malinowski & Gillespie, 2001;and Schmitz, 1997). Lower navigation-related anxiety has been correlated with frequent video game play (Tkacz & LaForce, 1998), accurate heading direction estimation in real-world (Lawton et al, 1996) and computerized navigation tasks (Mueller et al, 2009), faster completion and fewer errors in a model town navigation task (Hund & Minarik, 2009), faster completion of a real-world maze (Schmitz, 1997), and preference for route vs. landmark-based navigation (Schmitz, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Others have previously reported higher spatial anxiety, as measured by the SAS or questionnaires specific to the individual study, in women compared to men (Bryant, 1982;Castelli et al, 2008;Gabriel et al, 2011;Lawton, 1994;Lawton & Kallai, 2002;Malinowski & Gillespie, 2001;and Schmitz, 1997). Lower navigation-related anxiety has been correlated with frequent video game play (Tkacz & LaForce, 1998), accurate heading direction estimation in real-world (Lawton et al, 1996) and computerized navigation tasks (Mueller et al, 2009), faster completion and fewer errors in a model town navigation task (Hund & Minarik, 2009), faster completion of a real-world maze (Schmitz, 1997), and preference for route vs. landmark-based navigation (Schmitz, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Men report a preference for orientation-based (e.g., cardinal directions), whereas women report a preference for routebased (e.g., left-right turns) wayfinding strategies (e.g., Lawton, 1994). Men score lower than women on measures of environmental navigation-related anxiety (Bryant, 1982;Castelli, Corazzini, & Giuliano, 2008;Gabriel, Hong, Chandra, Lonborg, & Barkley, 2011;Lawton, 1994;Lawton & Kallai, 2002;Malinowski & Gillespie, 2001;and Schmitz, 1997). Higher scores by men indicate they have a greater self-reported environmental spatial ability (e.g., sense of direction) than women (e.g., Turano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial anxiety is also experienced differently, with women showing greater spatial anxiety than men (Barkley & Dye, 2007;Gabriel, Hong, Chandra, Lonborg, & Barkley, 2011;Lawton & Kallai, 2002;Malinowski & Gillespie, 2001). It has been shown that the spatial performance and the effects of stress are negatively correlated (Quaiser-Pohl, Geiser, & Lehmann, 2006;Titze, Heil, & Jansen, 2008).…”
Section: Cognitive Mapmentioning
confidence: 99%
“…There are conflicting results on the effect of oestrogen levels in women during the different phases of their menstrual cycle and their spatial performance (Chiarello, McMahon, & Schaefer, 1989;Gabriel et al, 2011;Halpern & Tan, 2001). Brain organization has also been attributed to the differences in the spatial performance.…”
Section: Route Selectionmentioning
confidence: 99%
See 1 more Smart Citation